A Critique of the Book an Introduction to Research in Family Sociology in Iran - Mahsa Larijani; Khadijeh Safiri (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
An introduction to research in family sociology in Iran has been written by Abbas Abdi with the aim of studying the evolution of the family and emphasizing the research dimension of the family. The purpose of this article is to examine the various dimensions of this book with a critical approach that is based on the conventional pattern of critical essays. The findings of the present article show that the criticisms of the book are in informal, structural and content areas, the most important of which include the lack of objective examples of claims and theories, lack of up-to-date sources, poor demographic analysis and lack of focus on topics such as the Ethics roots of the family and so on. Accordingly, this article, focusing on the formal and content dimensions of the work and relying on research citations, has tried to add to the richness of the book’s topics.